A method-comparison study regarding the validity and reliability of the Lactate Plus analyzer. Issue 2 (27th February 2013) - Hart, Sarah; Drevets, Kathryn; Alford, Micah; Salacinski, Amanda; Hunt, Brian E
Abstract : Objectives: The aims of this study were to: (1) determine the validity and reliability of the Nova Biomedical Lactate Plus portable analyzer, and quantify any fixed or proportional bias; (2) determine the effect of any bias on the determination of the lactate threshold and (3) determine the effect that blood sampling methods have on validity and reliability. Design: In this method comparison study we compared blood lactate concentration measured using the Lactate Plus portable analyzer to lactate concentration measured by a reference analyzer, the YSI 2300. Setting: University campus in the USA. Participants: Fifteen active men and women performed a discontinuous graded exercise test to volitional exhaustion on a motorised treadmill. Blood samples were taken via finger prick and collected in microcapillary tubes for analysis by the reference instrument at the end of each stage. Duplicate samples for the portable analyzer were either taken directly from the finger or from the micro capillary tubes. Primary outcome measurements: Ordinary least products regressions were used to assess validity, reliability and bias in the portable analyzer. Lactate threshold was determined by visual inspection. Results: Though measurements from both instruments were correlated (r=0.91), the differences between instruments had large variability (SD=1.45 mM/l) when blood was sampled directly from finger. This variability was reduced by ∼95% when both instruments measured blood collected in the capillary tubes. As the proportional and fixed bias between instruments was small, there was no difference in estimates of the lactate threshold between instruments. Reliability for the portable instrument was strong (r=0.99, p<0.05) with no proportional bias (slope=1.02) and small fixed bias (−0.19 mM/l). Conclusions: The Lactate Plus analyzer provides accurate and reproducible measurements of blood lactate concentration that can be used to estimate workloads corresponding to blood lactate transitions or any absolute lactate concentrations.